2016
DOI: 10.4103/0019-5154.193665
|View full text |Cite
|
Sign up to set email alerts
|

A clinicopathological analysis of primary cutaneous lymphomas: A 6-year observational study at a tertiary care center of south India

Abstract: Background:Little data are available concerning clinical and pathological patterns of cutaneous lymphomas in India.Aim:To analyze the clinical and histopathological characteristics of cutaneous lymphomas in Indian patientsMaterials and Methods:This is a single-center, prospective, observational study carried out from January 1, 2010, to December 31, 2015. The patients underwent clinical examination, human T-cell lymphotropic virus-1 (HTLV-1) screening, skin biopsy with hematoxylin and eosin and immunohistochem… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
8
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(9 citation statements)
references
References 30 publications
1
8
0
Order By: Relevance
“…Male preponderance was noted with the mean age being 61.9 years. In a six-year study of 35 cases of cutaneous T cell lymphomas by Khader et al .,[ 18 ] the authors report similar male preponderance and a mean age of onset of 52.66 years. Majority of cases in their study were of T cell Lymphoma (94.3%).…”
Section: Discussionmentioning
confidence: 76%
“…Male preponderance was noted with the mean age being 61.9 years. In a six-year study of 35 cases of cutaneous T cell lymphomas by Khader et al .,[ 18 ] the authors report similar male preponderance and a mean age of onset of 52.66 years. Majority of cases in their study were of T cell Lymphoma (94.3%).…”
Section: Discussionmentioning
confidence: 76%
“…A similar study from South India by Khader et al . [ 14 ] among 35 cases also showed various types of lesions in CTCL. In our study, we found predominantly superficial dermal involvement in 13/21 (61.9%) of cases of CTCL.…”
Section: Discussionmentioning
confidence: 98%
“…A similar study from South India by Khader et al . [ 14 ] showed a male-to-female ratio of 2.5:1, and the age ranged from 30–91 years with a median age of 53 years.…”
Section: Discussionmentioning
confidence: 99%
“…We found that type of lesions were mycosis fungoides in 42, adult T-cell lymphoma/leukemia in 30 and peripheral T-cell lymphoma in 10 patients. Khader et al [9] conducted a study among 35 cases, 33 (94.3%) were T-cell, and 2 (5.7%) were B-cell lymphomas. The mean age was 52.66, and the male to female ratio was 2.…”
Section: Discussionmentioning
confidence: 99%